Advancements in Nanocarrier Systems for Nose-to-Brain Drug Delivery - Thi-Thao-Linh Nguyen; Van-An Duong (Pharmaceuticals)
In recent decades, nose-to-brain drug delivery has shown effectiveness in treating many central nervous system diseases. Intranasally administered drugs can be delivered to the brain through the olfactory and trigeminal pathways that bypass the blood–brain barrier. However, nose-to-brain drug delivery is challenging due to the inadequate nasal mucosa absorption of drugs and the short retention time of the intranasal formulations. These problems can be minimized through the use of nano-drug delivery systems, such as micelles, polymeric nanoparticles, nanoemulsions, liposomes, solid lipid nanoparticles, and nanostructured lipid carriers. They can enhance the drug’s bioavailability in the brain via increases in drug solubility, permeation, and stability. Nose-to-brain nano-drug delivery systems have been evaluated in vivo by a number of research groups. This review aims to provide an overview of nose-to-brain delivery and recent advances in the development of nano-drug delivery systems for delivering drugs from the nose to the brain to improve the treatment of some central nervous system diseases.